AN ANALYSIS OF COMMON ERRORS IN ENGLISH MADE BY STUDENTS OF THE FOURTH SEMESTER IN THE FACULTY OF LANGUAGES AND CULTURES IN THE ACADEMIC YEAR OF 2021/2022 - Roesitha D M Syuriadi (LINGUAMEDIA Journal, 2021)
This study was conducted to find out common errors in English made by students of the fourth semester in the Faculty of Languages and Cultures in the academic year of 2021/2022. The research method used is the descriptive qualitative method. Thornbury and Richard theory becomes the main key in this research. The result of this research showed that 544 items of grammatical errors. The most frequent type of grammatical error is verb tense with the total number is 137 items or 6,3 %. The second is errors of article which consist of 123 items or 5,6%. The next are errors of pronoun (97 items or 4.3%), errors of preposition (77 items or 3.3 %), errors of capitalization (60 items or 2,6%), errors of subject-verbÂ  agreement (30 items or 1,3%) and finally is errors of spelling as the least number of errors with 20 items or 1%.